2022
DOI: 10.1111/bjep.12488
|View full text |Cite
|
Sign up to set email alerts
|

Relations between prior school performance and later test anxiety during the transition to secondary school

Abstract: Background. When exposed to evaluative situations, up to 40% of students develop test anxiety, reflected, namely, by extensive worry, intrusive thoughts, and physiological arousal. Though the negative influence of test anxiety on later school performance is well documented, the role of students' initial achievement in the development of later test anxiety is less clear.Aims and Sample. To better capture the nature of the relations between prior mathematics and language arts achievement and later test anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Second, contrary to the common belief that high-performing students (who tend to be overrepresented in private schools; Desjardins et al, 2009 ), are more susceptible to test anxiety than low performers because of the competitive pressure to perform more than others ( Kamanzi, 2019 ), this study showed that students from public schools were more susceptible to both forms of anxiety than those from private schools. These results are consistent with those of a recent study conducted among a similar sample of Quebec students in Canada, which found that most students who experience high levels of test anxiety are low achievers ( Plante et al, 2022 ). Indeed, as low-achieving students fail exams or courses more often than high achievers, they face more challenges in school.…”
Section: Discussionsupporting
confidence: 92%
“…Second, contrary to the common belief that high-performing students (who tend to be overrepresented in private schools; Desjardins et al, 2009 ), are more susceptible to test anxiety than low performers because of the competitive pressure to perform more than others ( Kamanzi, 2019 ), this study showed that students from public schools were more susceptible to both forms of anxiety than those from private schools. These results are consistent with those of a recent study conducted among a similar sample of Quebec students in Canada, which found that most students who experience high levels of test anxiety are low achievers ( Plante et al, 2022 ). Indeed, as low-achieving students fail exams or courses more often than high achievers, they face more challenges in school.…”
Section: Discussionsupporting
confidence: 92%
“…For boys, the negative link between mistakes in the threat condition and grades might mean that stereotype threat is occurring during regular school assessments, which over time could contribute to explain gender gaps in language arts performance. For girls, however, this result may instead stem from their greater tendency to experience test anxiety in response to evaluative pressure (Cassady & Johnson, 2002; Plante et al, 2022). Nevertheless, because similar links were observed among both boys and girls, future work is needed to replicate this result and support the assumption that language arts stereotype threat occurs in real‐world settings and contributes to gender gaps.…”
Section: Discussionmentioning
confidence: 99%
“…For boys, the negative link between mistakes in the threat condition and grades might mean that stereotype threat is occurring during regular school assessments, which over time could contribute to explain gender gaps in language arts performance. For girls, however, this result may instead stem from their greater tendency to experience test anxiety in response to evaluative pressure (Cassady & Johnson, 2002;Plante et al, 2022).…”
Section: Relations Between Stereotype Expressions and Gradesmentioning
confidence: 99%
“…Using such a domain-general approach (Vogelaar et al, 2017) in which test anxiety was viewed to be a situation-specific trait (Putwain et al, 2021) allows researchers to capture a broader perspective of test anxiety experienced in schools (Fréchette-Simard et al, 2022), which is manifest during various formal evaluative/testing situations in all subject areas (e.g., mathematics, science, literature). Researchers using a domain-general approach to test anxiety have reported that 40% of school-aged children suffer from test anxiety at a moderate level (Plante et al, 2022), while the proportion of elementary and secondary school students who experienced high levels of test anxiety may range from as little as 10% to as much as 30% (Segool et al, 2013). Given these widely varying distributions of test anxiety in typical classrooms, the domain-general approach appears to be particularly relevant for examining the relations between test anxiety and other indicators that are both specific (e.g., mathematics achievement) and unspecific (e.g., metacognition) to a domain, which is the case in the current study.…”
Section: Introductionmentioning
confidence: 99%